SEOM-AEEMT consensus on occupational cancer and cancer-associated disability - Mezquita, Laura; Vicente-Herrero, Mª Teófila; Cruz, Patricia; Ramírez Íñiguez de la Torre, Mª Victoria; Hidalgo-Coloma, Julia; Capdevila García, Luisa; Gallego, Óscar; Calvo, Aitana; Martínez, Katerine; Pérez-Altozano, Javier; Molina, Raquel; García-Pardo, Miguel; et al. (Clinical and Translational Oncology, 2026)
Cancer is one of the main causes of morbidity and mortality in Spain and has a significant impact in the workplace, where exposure to carcinogens in the work environment can increase the risk of developing this disease. The lack of communication between oncologists and occupational physicians limits the accurate assessment of cancer as an occupational disease and as a cause of disability. In 2020, the Spanish Society of Medical Oncology (SEOM) and the Spanish Association of Occupational Medicine Specialists (AEEMT) launched a joint initiative to strengthen prevention, reporting, and management of occupa tional cancer. This consensus provides a structured framework for assessing the occupational origin of cancer, facilitating case notification and classification as occupational contingencies, and supporting informed evaluations of disability and work reintegration in patients with cancer. The collaboration between both societies aims not only to advance occupational cancer prevention but also to promote evidence-based strategies for return-to-work planning.
Keywords: occupational cancer; occupational medicine; occupational risk factor; oncology; occupational carcinogen; disability